Identificación de Bacillus spp mediante matrix assisted laser desorption ionization-time of flight-mass spectrometry (MALDI-TOF MS) - Borges, Edgardo Maximiliano (2016)
Fil: Borges, Edgardo Maximiliano. Universidad Nacional del Nordeste. Instituto de Medicina Regional; Argentina.